2022
DOI: 10.3390/jcm11061509
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Application of Super-Saturated Oxygen to Reduce Infarct Size Following Myocardial Infarction

Abstract: Optimal medical therapy for secondary prevention following acute myocardial infarction reduces non-fatal ischaemic events. Intensive antithrombotic or lipid-lowering approaches have failed to significantly lower mortality. In the past, reduction of infarct size in patients undergoing primary percutaneous revascularisation for acute myocardial infarction had been considered as a surrogate outcome marker. However, infarct size measured by magnetic resonance imaging or SPECT is strongly associated with all-cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The 2019 IC-HOT trial demonstrated the feasibility and safety of transfusion of SSO via the left main coronary artery [ 110 ]. Starting in 2021, the TherOx ® device has been routinely used as an adjunctive therapy for myocardial infarction at the Hannover Medical School [ 111 ]. In the same year, the ISO-SHOCK trial, which evaluated the administration of SSO 2 into the coronary arteries of patients with acute myocardial infarction and cardiogenic shock, was initiated with an anticipated completion date of 2025.…”
Section: Cardiac Protection Strategiesmentioning
confidence: 99%
“…The 2019 IC-HOT trial demonstrated the feasibility and safety of transfusion of SSO via the left main coronary artery [ 110 ]. Starting in 2021, the TherOx ® device has been routinely used as an adjunctive therapy for myocardial infarction at the Hannover Medical School [ 111 ]. In the same year, the ISO-SHOCK trial, which evaluated the administration of SSO 2 into the coronary arteries of patients with acute myocardial infarction and cardiogenic shock, was initiated with an anticipated completion date of 2025.…”
Section: Cardiac Protection Strategiesmentioning
confidence: 99%
“…One of the major advantages of SSO 2 over other methods for reducing infarct size during acute STEMI treatment in the cath-lab is that it can be started after successful revascularization, without delaying primary PCI. This is in contrast to other methods such as LV unloading by Impella or therapeutic hypothermia, which may require additional steps or procedures that could delay the primary treatment ( Table 1 ) [ 61 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
“…This may enhance its cardioprotective effects. These therapies are also discussed in this special issue, Interventional Cardiology: Current Challenges in Acute Myocardial Infarction [40]. Studies on combinations of such therapies are necessary in order to clarify this position.…”
Section: The Future Of Therapeutic Hypothermia In Stemimentioning
confidence: 99%